Reduction factors to evaluate acceleration demand of soil-foundation-structure systems. Issue 109 (June 2018) - Karatzetzou, Anna; Pitilakis, Dimitris
Abstract: The seismic acceleration loading of structures founded on compliant soil is investigated through numerical elastic time history analyses of coupled soil-foundation-structure (SFS) systems and appropriate reduction factors of acceleration demand for free-field to evaluate acceleration demand for the SFS systems are proposed. The proposed reduction factors are the division of the acceleration demand for the coupled SFS system over the acceleration demand for the free-field, and propose an alternative method to calculate the actual acceleration loading considering interaction effects. The advantages of the proposed methodology are i) its accuracy, as the reduction factors result from coupled SFS numerical finite element analyses and consider both inertial and kinematic interaction effects and ii) its practicality, as it can be applied by the user performing no finite element numerical analysis. Additionally, the presented methodology can be applied to systems with important mass (e.g. bridge structures). The proposed acceleration reduction factors are presented in terms of dimensionless engineering parameters such as soil to structure stiffness ratio and the structure's aspect ratio. The accuracy, efficiency, and practicality of the proposed methodology are highlighted through an application to a typical bridge structure. Because structures with surface foundations are examined, inertial interaction mainly affects the acceleration demand. Therefore, the proposed reduction factors clearly demonstrate and quantify the beneficial effect of damping on buildings and bridges, as the maximum average acceleration at the top of the actual SFS system can reduce to about 55–85% of the acceleration demand for the free-field motion. Highlights: Maximum acceleration at the top of the actual SFS system is reduced due to SSI. Earthquake characteristics have a minor effect on the acceleration reduction factor. The presented quantitative evaluation of damping is more accurate. The proposed reduction factors can be very easily used in engineering practice.